Pengaruh Literasi Keuangan dan Financial Self-Efficacy terhadap Risky Credit Behaviour dalam Penggunaan PayLater - Nadya Surya; Evelyn Evelyn (Jurnal Manajemen dan Keuangan, 2023)
This study aims to determine the effect of Financial Literacy and Financial self efficacy on Risky credit behaviour in the usage of pay later feature. In addition, this study also aims to determine the mediating effect of Financial self-efficacy between financial literacy and risky credit behaviour. The population of this study is Indonesia Millenials and the sample of this study is residents born between 1990-2000 who have used pay later in the last 1 year. The data analysis was performed using Partial Least Square method. The results of the study indicate that objective financial literacy and subjective financial literacy have positive and significant effects on Financial self-efficacy, Financial self efficacy has negatif significant effects on risky credit behaviour, objective financial literacy and subjective financial literacy have negatif significant effects on risky credit behaviour, and Financial self-efficacy mediates the effects of subjective financial literacy and objective financial literacy on risky credit behavior.